Um novo espécime de Procolophon owen, 1876 (parareptilia, procolophonidae) para o triássico inferior sulbrasileiro - Neves, Eduardo Silva (2018)
This dissertation presents information regarding a new skull (CAPPA / UFSM 0189), with mandible in occlusion, ascribed to Procolophon trigoniceps. CAPPA/UFSM 0189 was collected in the municipality of São Francisco de Assis, Rio Grande do Sul, (Sítio Bica São Tomé). The preliminar taxonomic attribution of the specimen to the genus Procolophon was based on the molariform teeth, which presents a labiolingual expansion; the contact between the prefrontal, the frontal and the parietal; and the presence of the posterior border of the orbitotemporal fenestra with of the posterior border of the pineal foramen. The assignment to P. trigoniceps was based on the presence of eight maxillary bicuspid teeth and a wide rounded subtemporal margin. The aim of this project was the description of the cranial anatomy of the specimen and its taxonomic identification at the less possible level. Although P. trigoniceps is a well known species with a large number of specimens in collections from different countries, description of this material, the first nearly complete collected in Brazil, corroborates de presence of this taxon in this region of Gondwana, as previous studies carried out in this territory were based on incomplete specimens in comparison with CAPPA/UFSM 0189.